POLA PEMBINAAN ATLET ANGGAR PROVINSI RIAU DALAM KEIKUTSERTAAN PON XX - Fajri, Muhammad; Wijayanti, Ni Putu Nita; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the pattern of coaching for the Riau Province Fencing Athletes in the Participation of XX PON. This study is a quantitative descriptive study with a population of 15 athletes in PON XX. The sampling technique in this research is total sampling. Data was collected using observation, questionnaires and documentation. Test the validity of the instrument using the product moment with a significant level of 5% and the reliability test of the instrument using the alpha cronbach through the IBM SPSS Statistics 22 .Value Cronbach's Alpha 0.976. The results showed that the percentage of recruitment system factors was 17.70%, the percentage of training program factors was 21.81%, the percentage of trainers was 5.25%, the percentage of motivational factors was 12.89%, the percentage of confidence factors was 15.78%, and the percentage of facilities and infrastructure factors was 15.88%. Thus the pattern of coaching for the Riau Province's Fencing Athletes in the Participation of PON XX is 89.31% with a very good score interpretation.Key Words: Construction Patterns,Athletes, Riau Fencing, PON XX